Biallelic variants in WARS1 cause a highly variable neurodevelopmental syndrome and implicate a critical exon for normal auditory function. Issue 10 (21st July 2022) - Lin, Sheng‐Jia; Vona, Barbara; Porter, Hillary M.; Izadi, Mahmoud; Huang, Kevin; Lacassie, Yves; Rosenfeld, Jill A.; Khan, Saadullah; Petree, Cassidy; Ali, Tayyiba A.; Muhammad, Nazif; Khan, Sher A.; et al.
Abstract: Aminoacyl‐tRNA synthetases (ARSs) are essential enzymes for faithful assignment of amino acids to their cognate tRNA. Variants in ARS genes are frequently associated with clinically heterogeneous phenotypes in humans and follow both autosomal dominant or recessive inheritance patterns in many instances. Variants in tryptophanyl‐tRNA synthetase 1 ( WARS1 ) cause autosomal dominantly inherited distal hereditary motor neuropathy and Charcot‐Marie‐Tooth disease. Presently, only one family with biallelic WARS1 variants has been described. We present three affected individuals from two families with biallelic variants (p.Met1? and p.(Asp419Asn)) in WARS1, showing varying severities of developmental delay and intellectual disability. Hearing impairment and microcephaly, as well as abnormalities of the brain, skeletal system, movement/gait, and behavior were variable features. Phenotyping of knocked down wars‐1 in a Caenorhabditis elegans model showed depletion is associated with defects in germ cell development. A wars1 knockout vertebrate model recapitulates the human clinical phenotypes, confirms variant pathogenicity, and uncovers evidence implicating the p.Met1? variant as potentially impacting an exon critical for normal hearing. Together, our findings provide consolidating evidence for biallelic disruption of WARS1 as causal for an autosomal recessive neurodevelopmental syndrome and present a vertebrate model that recapitulates key phenotypes observed in patients. Abstract : Homozygous WARS1 variants have been identified in individuals with syndromic neurodevelopmental and hearing phenotypes. Here, we performed functional studies in Caenorhabditis elegans and zebrafish.